Using of mHealth in the Management of Stroke Risk Factors as Stroke Prevention Efforts : Literature Review: Penggunaan mHealth Dalam Manajemen Faktor Risiko Sebagai Upaya Pencegahan Stroke : Literature Review - eni_marwanti; Masfuri (Politeknik Kesehatan Kemenkes RI Jakarta I, 2023)
Stroke is a leading cause of death and disability in the world. Despite advances in stroke treatment, only limited number of patients are eligible for these medical and endovascular intervention. Additionally the outcome are unfavoranble for many indiviuals. Therefore stroke prevention is crucial. Various innovations have been created to make life easier, one of which is mHealth, which refers to the use of mobile devices to support health services. The aimed of this study is to evaluate the use of mHealth in managing risk factors as prevention stroke efforts. This study was used the PRISMA method with keyword adult at risk of stroke, mHealth intervention and stoke prevention. Articles were collected from databased online from 2019 to 2023. There are four qualify experimental articles for this topic. There is one article about using mHealth for screening atrial fibrillation, 2 articles about mHealth for activity and lifestyle promotion, and 1 article about mHealth to improve medication adherence of DM and decrease atherosclerotic vasculardisease (ASCVD) score. mHealth is potentially useful for individual at risk of stroke. Further research is needed to determine to which mHealth can be accessed and utilized by various population, as well as the security and user privacy aspect.